Audio for single camera operation - Grant, Tony (Oxford : Focal Press, 2003)
This volume provides an ideal grounding for anyone wanting to learn about the basics of recording sound, specific to broadcast single camera location work
Includes bibliographical references
Keywords: Sound -- Recording and reproducing; Video recording